1987
DOI: 10.1002/hed.2890100104
|View full text |Cite
|
Sign up to set email alerts
|

Lymph node invasion in hypopharynx and lateral epilarynx carcinoma: A prognostic factor

Abstract: Hypopharynx (HC: pyriform fossa, postcricoïd area, and posterior wall) and lateral epilarynx carcinomas (LEC: aryepiglottic fold, pharyngoepiglottic fold, and arytenoïd) have a high tendency to cervical lymph node invasion. Such nodal extension is a well-known prognostic factor. This study is based on a retrospective review of 884 clinical records of previously untreated HC or LEC. Seventy percent of patients revealed palpable nodes at their first examination, with a higher percentage for HC (73%) than LEC (62… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(39 citation statements)
references
References 8 publications
2
36
1
Order By: Relevance
“…In a univariate analysis, they noted that ECS and greater than 3 positive nodes were highly associated with DM (p < .001). In a retrospective review of patients with hypopharynx and larynx cancers who underwent varied treatments, Lefebvre et al 14 noted that patients with greater than 3 nodal metastasis and ECS had approximately 3 times the incidence of DM as compared to patients with no lymph node metastasis. They suggested that patients with these histological features be given more aggressive therapy.…”
Section: Discussionmentioning
confidence: 98%
“…In a univariate analysis, they noted that ECS and greater than 3 positive nodes were highly associated with DM (p < .001). In a retrospective review of patients with hypopharynx and larynx cancers who underwent varied treatments, Lefebvre et al 14 noted that patients with greater than 3 nodal metastasis and ECS had approximately 3 times the incidence of DM as compared to patients with no lymph node metastasis. They suggested that patients with these histological features be given more aggressive therapy.…”
Section: Discussionmentioning
confidence: 98%
“…More than 75% of patients with hypopharyngeal cancer are at an advanced stage at the time of diagnosis (14). Lymph node metastasis is present in 60-80% of patients and it directly affects the prognosis of this disease (15). Metastasis of tumors is a complex process, and various factors are involved in each step of metastasis (16).…”
Section: Introductionmentioning
confidence: 99%
“…More than 75% of patients with hypopharyngeal cancer are at an advanced stage at the time of diagnosis (1). Lymph node metastasis is present in 60-80% of patients and it directly affects the prognosis of the disease (2). Although the locoregional control of this cancer has been significantly improved in the last decades because of the advent of new surgical techniques and approaches, this improvement does not significantly influence the overall survival rate, partly because of metastasis (3).…”
Section: Introductionmentioning
confidence: 99%